Culture, Diversity, and the Welfare State - Klaus Gründler; Sebastian Köllner (Center for Economic Studies and ifo Institute (CESifo), 2018)
We show that culture and diversity strongly influence welfare systems around the globe. To disentangle culture from institutions, we employ regional instruments as well as data on the prevalence of the pathogen Toxoplasma Gondii, linguistic differences, and the frequency of blood types. The generosity of the welfare system is higher in countries with loose family ties and individualistic attitudes, high prevalence of trust and tolerance, and low acceptance of unequally distributed power. Apart from their direct effects, these traits also exert indirect impact by influencing the transmission of inequality to redistribution. Finally, we show that redistribution and diversity are linked non-linearly: moderate levels of diversity impede redistribution, while higher levels offset the negative effect.
Keywords: H11; I38; Z10; D31; 330; culture; redistribution; diversity